2020
DOI: 10.1002/hyp.13998
|View full text |Cite
|
Sign up to set email alerts
|

A soil moisture monitoring network to assess controls on runoff generation during atmospheric river events

Abstract: Soil moisture is a key modifier of runoff generation from rainfall excess, including during extreme precipitation events associated with Atmospheric Rivers (ARs). This paper presents a new, publicly available dataset from a soil moisture monitoring network in Northern California's Russian River Basin, designed to assess soil moisture controls on runoff generation under AR conditions. The observations consist of 2-min volumetric soil mois

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…This runoff generation process is referred to as the saturation-excess runoff. Q/P (%) of a watershed will become larger when effective soil water-storage is reducing [19][20][21][22]. Even a medium-sized storm event over a saturated watershed with a high runoff coefficient may cause severe flooding; therefore, it is critical to assess the performance of different runoff models under different runoff coefficient conditions in order to select the best performing parsimonious urban rainfall-runoff model for urban runoff estimation.…”
Section: Methodology and Study Sitementioning
confidence: 99%
“…This runoff generation process is referred to as the saturation-excess runoff. Q/P (%) of a watershed will become larger when effective soil water-storage is reducing [19][20][21][22]. Even a medium-sized storm event over a saturated watershed with a high runoff coefficient may cause severe flooding; therefore, it is critical to assess the performance of different runoff models under different runoff coefficient conditions in order to select the best performing parsimonious urban rainfall-runoff model for urban runoff estimation.…”
Section: Methodology and Study Sitementioning
confidence: 99%
“…Contrarily, some reported that the usage of CN in representing a watershed is often contradictory in describing related land cover areas [13]. Some researchers still reported difficulty to calibrate the existing model [14,15] while other studies started to incorporate soil moisture and saturation-excess concepts in their modelling approach [16][17][18][19]. US researchers [2,20] were first to conduct large scale studies on the SCS CN model by analyzing more than half a million rainfall events across 24 states in the USA and reported an optimum λ = 0.05 to achieve better runoff modelling results than Equation (2) in USA.…”
Section: Introductionmentioning
confidence: 99%
“…For each event, event rising time was calculated as the time‐lag from the start of an event to the soil moisture peak. Event amplitude was calculated as the difference between the soil moisture values at their maximum and at the start of the event, normalized using estimated field capacity and wilting point at the station (defined in Section 3.1.6) as practiced by Sumargo et al (2021). Soil moisture was judged as not responding if there was no soil moisture peak detected.…”
Section: Methodsmentioning
confidence: 99%